1995
DOI: 10.1002/ajh.2830490405
|View full text |Cite
|
Sign up to set email alerts
|

Anabolic‐Androgenic steroid abuse in weight lifters: Evidence for activation of the hemostatic system

Abstract: Anabolic-androgenic steroid abuse has recently been linked with acute vascular events in athletes. To date, the relationship between steroid abuse and the potential for cardiovascular disease has been considered almost exclusively in terms of lipid metabolism. However, recent reports of thrombosis in androgen abusing athletes with no evidence of atherosclerosis suggests the hypothesis that thrombosis risk in such athletes could be mediated through androgen induced abnormalities of coagulation. To determine if … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
43
0
2

Year Published

1999
1999
2016
2016

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 69 publications
(47 citation statements)
references
References 41 publications
2
43
0
2
Order By: Relevance
“…It has been shown in many oncological and myocardial remodelling studies that radiotracers based on RGD can be applied targeting avb3 integrin [42,43]. One recent report showed that 18 F-RGD PET can show atherosclerotic changes in apoE ) ⁄ ) mice [44]. In that report, quantified measures of 18 F-RGD uptake were correlated with 18 F-FDG PET measures.…”
Section: Vascular Imaging: Imaging Adhesion Molecules Expressionmentioning
confidence: 92%
See 4 more Smart Citations
“…It has been shown in many oncological and myocardial remodelling studies that radiotracers based on RGD can be applied targeting avb3 integrin [42,43]. One recent report showed that 18 F-RGD PET can show atherosclerotic changes in apoE ) ⁄ ) mice [44]. In that report, quantified measures of 18 F-RGD uptake were correlated with 18 F-FDG PET measures.…”
Section: Vascular Imaging: Imaging Adhesion Molecules Expressionmentioning
confidence: 92%
“…VCAM-1-targeting nanoparticles have been used for signal enhancement in atheromatous arteries of apoE ) ⁄ ) mice, and MRI showed promising results [40]. Recently, the same group labelled the same tetrameric peptide with positron emitter 18 Fluoride for PET imaging and was able to demonstrate early atherosclerotic changes in apoE ) ⁄ ) mice [41].…”
Section: Vascular Imaging: Imaging Adhesion Molecules Expressionmentioning
confidence: 99%
See 3 more Smart Citations